1993
DOI: 10.1149/1.2220890
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate Enhancement of Heavy n‐ and p‐Type Doped Silicon Deposited by Atmospheric‐Pressure Chemical Vapor Deposition at Low Temperatures

Abstract: n and p-Type doping of epitaxially grown Si over the temperature range from 850~ to as low as 550~ was investigated in an atmospheric pressure reactor. P, As, and B could be incorporated into single-crystal silicon at levels exceeding the solid solubility at growth temperatures to levels greater than 1 • 102~ 3. Remarkably, each of the hydride dopant sources, PH3, ASH3, and B2H6, dramatically enhanced the growth rate of Si from dichlorosilane (DCS) at lower temperatures. Such results are unprecedented for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…Those conditions are known to yield highly doped n-type Si epilayers [6,10]. The benefit of using trisilane as a Si-precursor gas over that of using DCS is demonstrated in terms of the achievable active As concentration at high growth rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those conditions are known to yield highly doped n-type Si epilayers [6,10]. The benefit of using trisilane as a Si-precursor gas over that of using DCS is demonstrated in terms of the achievable active As concentration at high growth rate.…”
Section: Resultsmentioning
confidence: 99%
“…Agnello et al showed that low-temperature CVD with dichlorosilane (DCS) and hydrogen as carrier gas leads to a very high dopant concentration. Deposition rate of about 10 nm/min had been obtained at a growth temperature of 700 8C [6]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Looking specifically at selective ALE in raised source/drain applications, the growth of in-situ-doped films could provide a path for additional scaling of R ext by improving e , ᮀ , R ac , and R sp . Epitaxial growth of in-situdoped films at low temperatures by CVD has already demonstrated very abrupt junction profiles because of the lack of implant damage combined with very low thermal cycles and incorporation of active dopants well above the solid solubility limit due to their incorporation on substitutional sites during growth [63]. In addition, junction abruptness is decoupled from the junction depth when a recess is combined with selective growth, as in the buried-source/drain [64] or recessed-junction approaches [12].…”
Section: Applications Of Ale Ald and Aletmentioning
confidence: 99%
“…Ϫ3 are achieved for P-and As-doped Si at low temperatures [63]. The chemical level of the dopants is two to five times greater than the active concentration, so hyperactivation of n-type impurities may also be achievable for n-FETs through the use of local strain engineering.…”
Section: Applications Of Ale Ald and Aletmentioning
confidence: 99%
“…For disilane, the addition of diborane (2 × 10 -4 of the disilane concentration) is reported to increase the deposition rate by more than a factor of 3 at lower temperatures, , although the effect decreases with increasing temperature. , For dichlorosilane, the addition of diborane (1 × 10 -3 of the dichlorosilane concentration) is reported to increase the deposition rate by 2 orders of magnitude . In contrast, for n-type dopants, the use of phosphine and arsine are reported to decrease deposition rates with silane, while increasing deposition rates with dichlorosilane …”
Section: Introductionmentioning
confidence: 99%